CRYSTAL CHEMISTRY OF SOME MG, CR, V NORMAL SPINELS FROM SLUDYANKA (LAKE BAIKAL, RUSSIA): THE INFLUENCE OF V3+ ON STRUCTURAL STABILITY - Lavina B.; Reznitskii L.Z.; Bosi F. (My University, 2003)
A suite of vanadian magnesiochromites from the Sludyanka metamorphic complex (South Lake Baikal, Russia) were investigated by means of X-ray single-crystal structural refinements and microprobe analyses. Various morphological types of Cr–V-bearing Mg spinels are located in calc–silicate metamorphic rocks, in an assemblage that also contains other Cr–V minerals such as escolaite–karelianite, uvarovite–goldmanite, Cr–V-bearing clinopyroxene, tourmaline, amphibole, mica, etc. Along the suite there is widespread V–Cr substitution (0.14 V3+ 0.95 afu, 1.02 Cr3+ 1.80 afu), and minor, variable Al contents. The Mg content of slightly lesser than 1 afu, is almost constant. Cell parameters and octahedral bond distances increase with V3+. Unexpectedly, the Mg–O tetrahedral bond distance also increases slowly with V3+. This weak dragging effect contributes towards maintaining distortion of the oxygen array with respect to the ideal CCP, thus providing a shielding effect, which reduces V3+–V3+ repulsion. This leads to the energetic stabilization of the structure, in spite of the increase of bond strain with increasing V3+ contents.
Keywords: Spinel; Crystal chemistry; Magnesiocoulsonite; V-magnesiochromite; Sludyanka